Literary Translation Theory in Brazil - Milton, John (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThis article will examine literary translation theory in Brazil. It will first look at the approach used by brothers Haroldo and Augusto de Campos, which could be considered as veritable translation school of thought. It will then examine other approaches.